2015
DOI: 10.1080/10941665.2015.1068189
|View full text |Cite
|
Sign up to set email alerts
|

HallyuRevisited: Challenges and Opportunities for the South Korean Tourism

Abstract: The tourism industry in South Korea has undergone unprecedented growth and faced multiple changes since 2000, thanks to the recent emergence and growing popularity and influence of the Hallyu phenomenon. Although an earlier research paper in Tourism Geographies in 2009 provided insights into the relationship between the Hallyu and patterns of inbound tourism, little scholarly effort has been made to investigate how the Korean tourism industry has evolved in response to the challenges and opportunities generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 43 publications
1
21
0
3
Order By: Relevance
“…In particular, Hallyu involving a K-drama, K-pop, and K-sports was significant. Added to that, the results for H2 indicated that destination image also had a significant positive effect on behavioral intention, which corroborates previous findings that destination image has a significant positive impact on behavioral intention [2]. H3 indicated that service quality had different perceptions of Hallyu and destination image.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In particular, Hallyu involving a K-drama, K-pop, and K-sports was significant. Added to that, the results for H2 indicated that destination image also had a significant positive effect on behavioral intention, which corroborates previous findings that destination image has a significant positive impact on behavioral intention [2]. H3 indicated that service quality had different perceptions of Hallyu and destination image.…”
Section: Discussionsupporting
confidence: 86%
“…In another study, Lee et al examined the involvement of Hallyu celebrities in Japan and found that they exerted a cognitive and emotional influence on Korea's tourist image as well as swayed intention to visit Korea. Kim and Nam [2] also suggested that Hallyu has a significant impact on the national image and behavioral intention. Among other findings, Lee, Lee and Jeon [3] observed that Korean celebrities, dramas, and music could play key roles in creating a positive national image for South Korea and shaping such behavioral intentions.…”
Section: The Relationship Between Hallyu Destination Image and Behamentioning
confidence: 99%
See 2 more Smart Citations
“…However, by combining the traditional culture with the limited tourism resources, South Korea can have the advantage of creating a unique Korean tourism [7]. For the years between 2007 and 2011, Chinese and Japanese tourist are the main Korean incoming tourism markets, which during those years take more than 50% of total tourists [8]. However, in 2011 in the incoming tourism from USA rank the third in Korea market.…”
Section: South Korea Tourism Industry and Muslim Touristsmentioning
confidence: 99%